Queen bee larva consumption improves sleep disorder and regulates gut microbiota in mice with PCPA-induced insomnia. (October 2021) - Tang, Qihe; Xiong, Jian; Wang, Jiaxuan; Cao, Zhe; Liao, Shiqun; Xiao, Yang; Tian, Wenli; Guo, Jun
Abstract: Untreated insomnia can harm physical and psychological health, ultimately affecting quality of life. This study aims to explore the beneficial effects of queen bee larva freeze-dried powder (QBLF) on p-chlorophenylalanine (PCPA)-induced insomnia and related neurotransmitter disorders and determine whether this improvement is related to the gut microbiota. The results showed that the γ-aminobutyric acid (GABA) and 5-hydroxytryptamine (5-HT) levels in the hypothalamus and serum were significantly decreased in the PCPA-induced insomnia group compared with the control group. QBLF treatment improved insomnia symptoms and significantly regulated GABA and 5-HT levels. Furthermore, QBLF modulated the gut microbiota composition and reversed insomnia-induced gut microbiota alterations, such as reduced relative abundances of Desulfovibrio, Alistipes and Lachnospiraceae sp. NK4A136 . Specifically, the relative abundance of Lactobacillus was significantly increased. Lactobacillus was positively correlated with insomnia-related neurotransmitter concentrations. Desulfovibrio, Alistipes and Lachnospiraceae sp. NK4A136 showed an opposite trend. Moreover, predictive function analysis revealed that QBLF modulated dysfunction due to PCPA-induced insomnia, such as significantly reduced gene expression related to the metabolism of cofactors and vitamins. Therefore, QBLF can ameliorate PCPA-induced insomnia and insomnia-related neurotransmitter disorders. Furthermore, the insomnia ameliorating effect of QBLF may relate to the regulation of the composition and structure of the gut microbiota in insomniac mice.